Ductility and internal forces redistribution in lightweight aggregate concrete beams - Waśniewski, Tomasz; Kołodziejczyk, Ewelina (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
Lightweight Aggregate Concrete (LWAC) is typically defined as concrete having a density smaller than or equal to 2200kg/m3 and can be obtained by mixing natural or artificial lightweight aggregates. There is a general scepticism regarding the use of lightweight aggregate concrete (LWAC) for structural applications. This concern is attached to the more brittle material behaviour which leads to lower ductility. This article presents a numerical parametric analysis of the behaviour of the reinforced LWAC cross-sections under the immediate load taking into account the density of the LWAC concrete, concrete strength and tensile reinforcement ratio. Numerical analysis of the beams was conducted in OpenSees, an open–source nonlinear finite element method framework. One-dimensional elements, with three degrees of freedom at each end, were used. Bending stiffness in the integration points was calculated based on the sectional moment – curvature relationship. The analysis showed that there is a relationship between the ductility of the cross-sections made of lightweight concrete and its density class. It is associated with limited compressive strains and the brittle behavior of LWAC. The limited rotation capacity of the reinforced concrete sections made of LWAC also affects the ability of redistribution of internal forces in statically indeterminate beams